Pengaruh Aktivitas Fisik Jalan Kaki Terhadap Kadar Gula Darah pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Cianjur Kota: The Influence of Walking Physical Activity on Blood Sugar Levels in Patients with Diabetes Mellitus in the Work Area of Cianjur City Health Center - Egi Permana; Siti Kamillah; Khrisna Wisnusakti (Journal of Nursing Education and Practice, 2021)
Introduction: Diabetes mellitus (DM) is a chronic disease that occurs because the pancreas cannot produce enough insulin or the body cannot effectively use the insulin produced by the pancreas. There are 4 ways to maintain blood glucose levels, namely; pharmacological therapy, nutritional therapy, diabetes self-management education, and physical activity. Walking exercise is the most often described as the modalities of physical activity to improve health. Objective: The research objective was to determine the effect of walking physical activity on blood sugar levels in diabetes mellitus patients in the work area of ​​the Cianjur City Health Center in 2021. Method: This study used a design quasi-experimental with an approach one-group pretest-posttest design. The population of this study was all 620 people with diabetes mellitus who were taken using a simple random sampling technique, which was 17 respondents. Results: Analysis of data using test paired sample t-test. Statistical test results obtained a p-value of 0.000 <0.05 so that Ha is accepted, which means there is an effect of physical activity on foot on blood sugar levels in diabetes mellitus patients in the work area of ​​the Cianjur City Health Center in 2021. Conclusion: This study found that walking exercise as far as 2,5 km for 30 minutes can lower blood sugar levels significantly in patients with diabetes mellitus.